1984
DOI: 10.2134/jeq1984.00472425001300040016x
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory Comparison of a Standardized Phosphorus Adsorption Procedure

Abstract: A standard P adsorption procedure was proposed and the ability of four laboratories to produce consistent results over a wide range of soils was determined. For this procedure, 0.5 to 1.0 g of soil were shaken in 0.01 mot L CaCI at a soil/solution ratio of 1:25 in containers allowing a 50% head space for 24 h at 24 to 26°C on an end-over-end shaker. Initial dissolved inorganic P concentrations of 0 to 323 smol P L (as KHPO4 or NaH1`04) were used and microbial activity inhibited by 20 g L chloroform. Excellent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
149
0
3

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(154 citation statements)
references
References 13 publications
2
149
0
3
Order By: Relevance
“…Similarly, Sharpley et al (6) found a close agreement between iron-oxide strip (Fe-strip) P measured by three different laboratories on a variety of soils (pH 5.5 to 8.0). Elsewhere, Nair et al (7) examined variability related to P adsorption procedures, reporting strong agreement in isotherm parameters as estimated by four laboratories for a wide range of soils (pH 5.6 -7.9).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Sharpley et al (6) found a close agreement between iron-oxide strip (Fe-strip) P measured by three different laboratories on a variety of soils (pH 5.5 to 8.0). Elsewhere, Nair et al (7) examined variability related to P adsorption procedures, reporting strong agreement in isotherm parameters as estimated by four laboratories for a wide range of soils (pH 5.6 -7.9).…”
Section: Introductionmentioning
confidence: 99%
“…Although less than 25% of the sorbed P was found in the non-labile pools, the Naoh+hCl fraction contributed 2 to 61% of the overall sorption strength estimated for the soils studied. The results of this study suggest that sorption strength calculated from sorption studies are heavily skewed toward the nonlabile fraction, which was found to constitute a very small portion of the binding sites occupied during sorption studies.Abbreviations: b, the sorption maximum; ICP-OES, inductively coupled plasma optical emission spectroscopy; b f , sorption maximum determined using the sequential fractionation data; b i , sorption maximum estimated using the method of Nair et al (1984); k, a coefficient unique to each soil that has been used as a measure of the sorption strength between soil particles and P; k f , the sorption strength parameter determined using the sequential fractionation data; k i , the sorption strength parameter estimated using the method of Nair et al (1984); OM, organic matter; P i , inorganic P; P o , organic P; W kft , cumulative weighted sorption strength. W hen P is added to soils in the form of fertilizer, a series of reactions takes place, ranging from diffusion of P from the fertilizer granules into the soil solution, sorption of P into soil particles, and, with time, P precipitation (Hedley and McLaughlin, 2005).…”
mentioning
confidence: 99%
“…To study the sorption capacity of soils, many researchers have used sorption studies, where a given amount of soil is mixed with solutions made up with various P concentrations (Nair et al, 1984). The amount of P adsorbed onto the soil is estimated as the difference between the initial and final solution P concentrations (Olsen and Watanabe 1957;Nair et al, 1984).…”
mentioning
confidence: 99%
See 2 more Smart Citations